Roof-Inhabiting Cousins of Rock-Inhabiting Fungi: Novel Melanized Microcolonial Fungal Species from Photocatalytically Reactive Subaerial Surfaces - Constantino Ruibal; Laura Selbmann; Serap Avci; Pedro M. Martin-Sanchez; Anna A. Gorbushina (Life, 2018)
Subaerial biofilms (SAB) are an important factor in weathering, biofouling, and biodeterioration of bare rocks, building materials, and solar panel surfaces. The realm of SAB is continually widened by modern materials, and the settlers on these exposed solid surfaces always include melanized, stress-tolerant microcolonial ascomycetes. After their first discovery on desert rock surfaces, these melanized chaetothyrialean and dothidealean ascomycetes have been found on Mediterranean monuments after biocidal treatments, Antarctic rocks and solar panels. New man-made modifications of surfaces (e.g., treatment with biocides or photocatalytically active layers) accommodate the exceptional stress-tolerance of microcolonial fungi and thus further select for this well-protected ecological group. Melanized fungal strains were isolated from a microbial community that developed on highly photocatalytic roof tiles after a long-term environmental exposure in a maritime-influenced region in northwestern Germany. Four of the isolated strains are described here as a novel species, Constantinomyces oldenburgensis, based on multilocus ITS, LSU, RPB2 gene phylogeny. Their closest relative is a still-unnamed rock-inhabiting strain TRN431, here described as C. patonensis. Both species cluster in Capnodiales, among typical melanized microcolonial rock fungi from different stress habitats, including Antarctica. These novel strains flourish in hostile conditions of highly oxidizing material surfaces, and shall be used in reference procedures in material testing.